Sustainability Reporting: Quality and Value Relevance - Nurzi Sebrina; Suhairi Suhairi; Suhanda Suhanda (Universitas Negeri Padang, 2022)
This study examines the quality of sustainability reporting of public companies listed on the Indonesia Stock Exchange and analyses the incremental value of sustainable reporting information (non-financial) on the value relevance of financial information. The research was conducted on the sustainability reporting of companies listed on the Indonesia Stock Exchange and from 713 listed companies, and by purposive sampling, a sample of 80 companies was obtained. Research on the quality of sustainability reports is carried out on reports published from 2016 to 2019. As for value relevance, it is carried out on sustainability reports published from 2016 to 2018. The significance of the value of information is investigated using the multiple regression method, modified Ohlson's (1995) model, while the quality of sustainability reporting is investigated using content analysis. The study shows that the quality of sustainability reporting is still low, determined by the disclosure index and the level of reliability. The quality of sustainability reporting and information on economic, environmental, social topics (except governance) is relevant for stakeholders. Thus, the research results related to the overall quality of sustainability reporting and the topics of sustainable performance are consistent with the value-enhancing theory in the context of the shared value concept. However, the sustainability report does not have a positive incremental value to the value relevance of financial information on companies listed on the Indonesia Stock Exchange. Investors should consider long-term sustainability rather than short-term financial performance. The findings can also be useful for policymakers when issuing rules for sustainable reporting because the results show that transparency is a relevant valueKeywords: Sustainability reporting, the value relevance of sustainability reporting information